Overcoming disadvantage in education - Gorard, Stephen; See, Beng Huat (Abingdon, Oxon : Routledge, Taylor & Francis Group, 2013)
'Governments, local authorities, school leaders, and teachers all over the world want to improve the attainment and participation of all students. They also want to minimise any systematic differences in educational outcomes between social and economic groups. However, considerable effort and money is being wasted on policies, practices and interventions that have very little hope of success, and that may indeed endanger the progress that is being made otherwise. The poor quality of much education research evidence, coupled with an unwillingness among users of evidence to discriminate appropriately between what we know and do not know, means that opportunities are being missed. At a time of reduced public spending and increased public unrest, at least in the UK, it is important that proposed interventions are both effective and efficient. Overcoming Disadvantage in Education is unique in the way it: - Shows where the solutions to underachievement and poverty lie - combines primary(new), secondary (official) and published (review) evidence - distinguishes between those possible causes of underachievement that are largely fixed for individuals, and those that are modifiable. There are evidence-informed ways forward in handling under-achievement and increasing social justice in education. This book shows which the more likely approaches are, and where further work could yield further benefits. This book will be a key text for developing academic researchers and supervisors in the social sciences'--
Includes bibliographical references (pages 167-200) and index.
Keywords: Educational equalization; Children with social disabilities -- Education